PENERAPAN FORUM RHJFOX MENGGUNAKAN METODE PHPBB SEBAGAI MEDIA PEMBELAJARAN PADA PERGURUAN TINGGI RAHARJA - Untung Rahardja; Yessi Frecilia; Noval Jindan (Universitas Raharja, 2015)
Developed technology rapidly becomes very important and indispensable in the world of education, education requires the media to support the teaching and learning process. The learning method is used to achieve the objectives of learning lecturer. One method that can be used by teachers in the learning process aimed at improvingthe ability of learners which method of discussion. Although many of the container orinstructional media for teaching and learning activities, a container of learning to use the forum is quite effective and very good to support the learning and teaching process, especially on the older students the process of analytical study usingn iLearning device i.e. the iPad on College Raharja. The current obstacle is the difficulty for many of the students use the media discussion of today's modern information technology. To overcome the various problems as described above, can be done by using additional applications in order to support teaching and learning activities using the forum RhjFox. then needed a quick and efficient process to resolve problems that occur above. Current teaching and learning just sitting and listening to the lecturer who was explaining before, unbeknownst to the students understand or are notexplained by the lecturer to even ask sometimes still shy